PERIBAHASA MELAYU DAN TERJEMAHANNYA DALAM BAHASA INGGERIS DARI ASPEK BUDAYA - Md Din, Nurul Asmaa Akmal; Awang Pawi, Awang Azman (JURNAL MELAYU SEDUNIA, 2020)
Malay proverb is a medium that old folks used to deliver a hidden messages. The concept of valuing courtesy and thoughtfulness is portrayed through the way the older generation speaks and uses the proverb. It also symbolizes the intellect possessed by the Malay community. This creates a gap for translators to understand the underlying meaning from the proverb as there is a huge difference between the Malay and English languages. Therefore, a thorough understanding on Malay proverb and its translation was carried out to observe the cultural differences between the Malay and English languages by using the culture-specific theory introduced by Peter Newmark (1988). Thus, the findings show that there are a lot of cultural elements used in Malay proverb.